Antioxidant and Neuroprotective Properties of Non-Centrifugal Cane Sugar and Other Sugarcane Derivatives in an In Vitro Induced Parkinson’s Model - Javier Cifuentes; Vivian A. Salazar; Mónica Cuellar; María Claudia Castellanos; Jader Rodríguez; Juan C. Cruz; Carolina Muñoz-Camargo (Antioxidants, 2021)
Non-centrifugal cane sugar (NCS) is a traditional sweetener in most sugarcane regions of the world. In Colombia, this product has a socio-economic importance due to the extensive cultivation area and the high consumption rate per capita. NCS traditional processing involves consecutive stages of thermal processing that begin with juice extraction, clarification, evaporation, and finish with syrup crystallization into a solid commercial product, identified as NCS. Sugarcane is known to have a natural content of polyphenols, amino acids, vitamins, minerals, and complex sugars, some of which are reported as antioxidant and antiproliferative agents thought to be responsible for the product’s bioactive profile. There is evidence to suggest that traditional thermal processing to obtain NCS leads to a considerable decrease in the contents of these bioactive compounds, mainly due to uncontrolled process variables such as temperature. Accordingly, the aim of this study was to assess and compare the bioactivity of sugarcane (SC) derivatives produced under controlled thermal conditions versus the traditional method. To achieve this goal, we evaluated the cytotoxic, antioxidant, and neuroprotective effects of varying concentrations of SC derivatives in an in vitro induced Parkinson’s model. Results demonstrate non-cytotoxic activity on the cellular model by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and LDH assays, even at the highest tested concentration of 8 mg/mL, for all SC derivatives. The effect of SC derivatives on the induced oxidative stress model showed a biological reversion and recovering effect of the mitochondrial membrane potential and a halting of the progress into the early apoptosis phase. In conclusion, we demonstrated that the bioactive compounds present in SC derivatives obtained by a process under controlled temperature conditions are largely preserved, and even their biological activities are enhanced compared with SC derivatives obtained by the traditional thermal evaporation of SC-juice.